Pre-treatment loss to follow-up among children with multidrug-resistant tuberculosis in South Africa, 2008–2010 - Moore, Brittany K.; Erasmus, Linda; Ershova, Julia; Smith, Sarah E.; Ndjeka, Norbert; Podewils, Laura J. (PloS one, 2020)
Multidrug-resistant (MDR) TB is more difficult to diagnose and treat compared with drug-susceptible TB. Young children are at greater risk of severe TB disease and death when treatment is delayed compared to adults. We sought to describe characteristics of children (<13 years) diagnosed with MDR TB between 2008-2010 in three South African provinces and assess factors associated with pre-treatment loss to follow-up. We matched laboratory and medical records at treatment facilities to identify pre-treatment loss and examined demographic and clinical characteristics for association with loss. Categorical variables were examined for association using Pearson's x2 or Fisher's exact test, employing Bonferroni correction for multiple pairwise comparisons. Between 2008-2010, 156 children were diagnosed with laboratory-confirmed MDR TB. Only 44% (n = 69) were documented as having received treatment. Young children (<2 years) (47/59, 80%), children with extrapulmonary (EP) TB (27/34, 79%), and children diagnosed at general hospitals (60/97, 62%) were most likely to be lost before treatment. Children most vulnerable to death from TB are most likely to be lost before treatment, possibly leading to underestimates of disease burden, case notifications, and poor outcomes among this population. Point-of-care diagnosis and robust follow-up may reduce pre-treatment loss in this population.